IMPLEMENTASI MANAJEMEN PEMBELAJARAN DALAM PELAKSANAAN KURIKULUM 2013 - Yuliah Saskomita (Manajer Pendididikan, 2015)
The objective of this research is to describe the implementation of instructional management in 2013 curriculum at elementary school number 01 of Bengkulu city. The research design is qualitative descriptive. The subjects of research are teachers, principal, vice-principal, and students. Data collecting techniques are interview, observation, and documentation. The conclusions are that the teachers have already understood the 2013 curriculum, that has been implemented by the syllabus the preparation of the lesson plans based on the 2013 curriculum lesson plans in form of Discovery Learning Activities, but in fact, the teachers sometimes have not performed the learning process to a student-oriented learning.Keywords: implementation, management, 2013 curriculum, elementary school